Usefulness of pleural fluid cholesterol in the diagnosis of tuberculous pleural effusion - Paul, Susanta Kumar; Ahmed, Shamim; Chakrabortty, Rajashish; Majumder, Shuvo; Sarker, Dip Jyoti; Kumar Paul, Shamrat; Islam, Samprity; Atiqur Rahman, Mohammed (International Journal of Research in Medical Sciences, 2023)
Background: Tuberculous pleural effusion (TPE) is the most common etiology of exudative pleural effusion in high tuberculosis burden countries like Bangladesh. The usefulness of pleural fluid cholesterol for the diagnosis of TPE is not evaluated yet. This study aimed to assess the usefulness of pleural fluid cholesterol for the diagnosis of TPE. Methods: This cross-sectional study was conducted at the department of respiratory medicine at Bangabandhu Sheikh Mujib medical university. A total of thirty-five TPE was included in this study. Pleural fluid aspiration followed by cytological (total count, differential count), and biochemical (protein, glucose, lactate dehydrogenase, adenosine deaminase, and cholesterol) investigations were done. At the same time, blood was sent for biochemical (protein, glucose, and lactate dehydrogenase) investigation. Pleural biopsy followed by a histopathological examination was done to confirm TPE. Ethical clearance was obtained from the institutional review board (IRB) prior to starting this study. Results: In our study, the mean age of the participants was 35.54±14.13 years, and male predominant (74.3%). The mean pleural fluid cholesterol was 99.87±23.82 mg/dl. With a cut of value 69.85, the sensitivity, specificity, and accuracy were 97.14%, 57.14%, and 77.14% respectively. Conclusions: Pleural fluid cholesterol has significant diagnostic usefulness for the diagnosis of tuberculous pleural effusion.